Composition and morphology tuning during hydrothermal synthesis of SrxBa1−xNb2O6 tetragonal tungsten bronzes studied by in situ X-ray diffraction. Issue 39 (16th September 2019) - Grendal, Ola G.; Blichfeld, Anders B.; Vu, Tuong D.; van Beek, Wouter; Selbach, Sverre M.; Grande, Tor; Einarsrud, Mari-Ann
Abstract : Advanced in situ techniques provide knowledge about crystal growth mechanisms of Sr x Ba1− x Nb2 O6 facilitating the design of the microstructure and the determination of stoichiometry. Abstract : Current interest in 1D ferroelectric materials calls for cheap, controllable, reproducible and environmentally friendly synthesis routes. Hydrothermal synthesis stands out as one of the most promising routes, but a thorough understanding of nucleation and growth mechanisms is needed for full utilization and control. Here, we present a new hydrothermal route for preparing Sr x Ba1− x Nb2 O6 ( x = 0.32–0.82, SBN) tetragonal tungsten bronzes. The nucleation and growth of SBN were studied by a combination of in situ synchrotron X-ray diffraction and ex situ scanning electron microscopy (SEM). Based on the in situ X-ray diffraction data, a nucleation mechanism is proposed where an amorphous precursor consisting of clusters with a mix of edge- and corner-sharing NbO6 octahedra undergoes gradual restructuring leading to more corner-sharing octahedra, before abrupt crystallization. For the first time, the Sr fraction in SBN was successfully tuned with a hydrothermal method, both by changing the Sr fraction in the precursor solutions and by changing the dielectric constant of the solvent. The morphology of SBN was successfully controlled by the synthesis temperature, where a low temperature (175 °C) resulted in rod-shaped particles (length ∼1.5 μm and ∼500 × 500 nm 2 cross section) and a higher temperature (300 °C) gave cube-shaped particles (∼500 × 500 nm 2 ).